(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article presents the general system of sets of connections of the design of the product and the production process. An algorithm and a flowchart for geometric modeling of the automated system "MICROSYS 25" for microsystems equipment products and a flowchart of an algorithm for selecting a technological process (TP) of the automated system have been developed.